Importance of Cytomegalovirus Mir-UL-148D Expression Pattern in Sexually Transmitted Diseases - Shibeeb, Buthana Thijeel; Karomi, Asma Sumiea; Humada, Yasser Hamad (American Journal of Biology and Natural Sciences, 2025)
Introduction & aim: Small, non-coding RNA molecules known as microRNAs (miRNAs) control post-transcriptional gene expression in almost all eukaryotic organisms as well as certain viruses, especially herpesviruses. Since the primary cause of morbidity in immunocompromised people is the human cytomegalovirus (HCMV), HCMV miRNAs could be useful targets for novel, much needed antiviral medications. Therefore, the current study aimed to evaluate the importance of Cytomegalovirus miR-UL-148D Expression Pattern in sexually transmitted diseases. Materials & methods: From January to May 2025, A total of 400 blood samples were collected from100 blood donors at the main blood bank in Kirkuk, 100 samples from people preparing to get married at the public health laboratory in Kirkuk city and 200 samples were collected from external dermatology and venereology clinics. 5 ml of blood was withdrawn and placed in a 2 ml TRIzol collection tube for molecular diagnosis and microRNA isolation. The remaining 3 ml was collected in a gel tube for serological examinations. Results: Among 400 samples tested using several methods for CMV detection, Table 1 shows that the CMV infection rate was 42.8% using the Rapid Strip, while the infection rate using ELISA was 20.3% for IgG and 2.5% for IgM. On the other hand, the rate using PCR was 3.3%, while the rate was 4.3% using RT-PCR. For gene expression, folding changes ranged from (0.768 to 1.164) in the control group, with an average of 1.009, while in patients, they ranged from (1.765 to 11.471) with an average of 3.808. The results showed a significant (P=0.001) increase in gene expression in patients compared to the control group. Conclusions: The significance of this viral miRNA as a biological biomarker of HCMV latent infection is demonstrated by the validation of the elevated miR-UL-148D expression level in the patients when compared to the control.